Faktor-Faktor yang Mempengaruhi Pengeluaran Rumah Tangga untuk Hewan Peliharaan; Studi Kasus di Kelurahan Padang Sambian - Pranatayasa, Made; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 11, November 2013 (pp. 492-546), 2013)
Expenses are essential thing in a household. Every household has their form or structure of consumption and different expenses. Lots of factors can affect household expenses, such as expenses for pet in particular. The aim of this study is to identify the affect of income, education, age, and environment to household expenses for pet at Padang Sambian Village both simultaneously and particularly. This study took 70 respondents which taken by Purposive Sampling method. Data collected is analysed by multiple linear regression technique. Based on analysis result is known that all variable; income, education, age, and environment significantly affecting household expenses for pet at Padang Sambian Village both simultaneously and particularly.
Keywords: income; education; age; environment; household expenses